Updated allele frequencies of SERPINB7 founder mutations in Asian patients with Nagashima-type palmoplantar keratosis/keratoderma. Issue 2 (August 2021) - Ito, Yasutoshi; Takeichi, Takuya; Ikeda, Kenta; Tanahashi, Kana; Yoshikawa, Takenori; Murase, Yuya; Muro, Yoshinao; Kawakami, Yoshio; Nakamura, Yasuo; Matsuyama, Kanako; Muto, Jun; Oiso, Naoki; et al.
Highlights: We reported 14 NPPK patients with biallelic SERPINB7 mutations, including one novel mutation p.Trp145Ser. The mutant allele frequency of the East Asian SERPINB7 founder mutation c.796C>T was 0.536 in the present 14 NPPK patients. 11 of the 14 (78.6 %) NPPK patients had the founder mutation. NPPK families with the founder mutation accounted for 85.9 % of the previously reported and present Japanese NPPK families. NPPK families with the founder mutation accounted for 87.6 % (78/89 families) of East Asian NPPK families.